Model Picture and Picture dengan Index Card Match terhadap Penguasaan Konsep Matematis - Khasanah, Nur; Netriwati, Netriwati; anggraini, Dian (Desimal: Jurnal Matematika, 2018)
The Mathematics curriculum that is implemented in teaching and learning activities in mathematics requires teachers to master what should be learned and to educate learners, motivate, inspire and give learners space to perform process skills. Therefore, the authors conducted research by using the collaboration model of Picture And Picture with Index Card Match on the mastery of mathematical concepts with the aim of knowing the Picture and Picture model with Index Card Match provides mastery of effective mathematical concepts than conventional models, whether or not there is a difference in mastery of mathematical concepts in learners who have high motivation, moderate and low, there is no interaction between learning models and motivation to learn mastery of mathematical concepts. This research is Quasi Eksperimen Design. The sampling technique in this research is by random class. Hypothesis testing using variance analysis of two different cell roads, with 5% significance level. Prior to hypothesis testing, prerequisite tests were performed, including normality test using liliefors test and homogeneity test with Barlett test. From the result of analysis obtained, so rejected. , so is rejected. , so is accepted. Obtained conclusion Collaboration Model Learning And Picture with Index Card Match provides the results of the mastery of an effective concept than the conventional model of 67.5%. In addition, there are differences in the mastery of mathematical concepts that are seen between high, medium and low motivation. Finally, there is no interaction between the learning model and the motivation to learn to master the mathematical concepts of learners.